Reconstructing meanings of the "discriminated Mangyan" towards an emancipatory educational framework - Pine, Elijah Jesse M.; Daya, Romel A. (2017)
Available historical accounts suggest the existence of discrimination against Mangyans in what is supposedly their ancestral island of Mindoro. Narratives of how they are discriminated against by many "lowlanders" (i.e, non-Mangyans now inhabiting and dominating Mindoro) persist until today. This study probed into the experiences of six Mangyan students of theTugdaan Mangyan Center for Learning and Development in Naujan, Oriental Mindoro about the discrimination they experienced from non-Mangyans. Guided by the Social Construction Theory, the study characterized the social world within which lowlanders historically discriminated against Mangyans, explored the Mangyan students' meanings of discrimination, and determined the communicative interactions that had been responsible for such construals of discrimination. Based on the results, the study crafted a working educational framework to counter discrimination against Mangyans, especially in the context of formal and nonformal education.
Keywords: Mangyans; Mangyan (Philippine people) -- discrimination